Politics of civil society Neoliberalism or Social Left? - Powell, Frederick (Bristol, 2007)
This is an indispensable book for anyone who wants to make sense of the bewildering recent shifts in ideology and policy towards the Welfare State - and to understand the broader political implications of civil society. "The Politics of Civil Society" offers a wide-ranging analysis of recent shifts in ideas and paradigms that underpin social policy. Since the 1980s, the renaissance of civil society has introduced new ideas about the nature of power, citizenship and human rights, with such slogans as 'active citizenship' and 'participation' radically challenging the dominance of the state, the power of professionals and the welfare system itself. Frederick Powell traces the historical roots of these apparent changes and movements, demonstrates in detail their often paradoxical results and speculates about the whole future of social policy. He has produced an entirely original synthesis, as well as a major guide to social policy, that goes well beyond traditional interpretations of civil society as the voluntary and community sector. The book covers a breadth of material which is not generally found in social policy literature and offers a unique opportunity to rethink existing paradigms
Keywords: Civil society